Biopolymer/glycopolypeptide-blended scaffolds: synthesis, characterization and cellular interactions - Dhaware, Vinita; Diaz, David Diaz; Sen Gupta, Sayam (Chemistry-An Asian Journal, 2019)
Three-dimensional (3D) scaffolds formed from natural biopolymers gelatin and chitosan that are chemically modified by galactose have shown improved hepatocyte adhesion, spheroid geometry and functions of the hepatocytes. Galactose specifically binds to the hepatocytes via the asialoglycoprotein receptor (ASGPR) and an increase in galactose density further improves the hepatocyte proliferation and functions. In this work, we aimed to increase the galactose density within the biopolymeric scaffold by physically blending the biopolymers chitosan and gelatin with an amphiphlic beta-galactose polypeptide (PPO-GP). PPO-GP, is a di-block copolymer with PPO and beta-galactose polypeptide, exhibits lower critical solution temperature and is entrapped within the scaffold through hydrophobic interactions. The uniform distribution of PPO-GP within the scaffold was confirmed by fluorescence microscopy. SEM and mechanical testing of the hybrid scaffolds indicated pore size, inter connectivity and compression modulus similar to the scaffolds made from 100 % biopolymer. The presence of the PPO-GP on the surface of the scaffold was tested monitoring the interaction of an analogous mannose containing PPO-GP scaffold and the mannose binding lectin Con-A. In vitro cell culture experiments with HepG2 cells were performed on GLN-GP and CTS-GP and their cellular response was compared with GLN and CTS scaffolds for a period of seven days. Within three days of culture the Hep G2 cells formed multicellular spheroids on GLN-GP and CTS-GP more efficiently than on the GLN and CTS scaffolds. The multicellular spheroids were also found to infiltrate more in GLN-GP and CTS-GP scaffolds and able to maintain their round morphology as observed by live/dead and SEM imaging.
Keywords: adhesion; Aggregates; Cellular infiltration; Spheroids

Clopidogrel eluting electrospun polyurethane/polyethylene glycol thromboresistant, hemocompatible nanofibrous scaffolds - Shitole, Ajinkya A.; Giram, Prabhanjan S.; Raut, Piyush W.; Rade, Priyanka P.; Khandwekar, Anand P.; Sharma, Neeti; Garnaik, Baijayantimala (Journal of Biomaterials Applications, 2019)
Biomaterials used as blood-contacting material must be hemocompatible and exhibit lower thrombotic potential while maintaining hemostasis and angiogenesis. With the aim of developing thromboresistant, hemocompatible nanofibrous scaffolds, polyurethane/polyethylene glycol scaffolds incorporated with 1, 5, and 10 wt% Clopidogrel were fabricated and evaluated for their physiochemical properties, biocompatibility, hemocompatibility, and antithrombotic potential. The results of physicochemical characterization revealed the fabrication of nanometer-sized scaffolds with smooth surfaces. The incorporation of both polyethylene glycol and Clopidogrel to polyurethane enhanced the hydrophilicity and water uptake potential of polyurethane/polyethylene glycol/Clopidogrel scaffolds. The dynamic mechanical analysis revealed the enhancement in mechanical strength of the polyurethane/polyethylene glycol scaffolds on incorporation of Clopidogrel. The polyurethane/polyethylene glycol/Clopidogrel scaffolds showed a tri-phasic drug release pattern. The results of hemocompatibility assessment demonstrated the excellent blood compatibility of the polyurethane/polyethylene glycol/Clopidogrel scaffolds, with the developed scaffolds exhibiting lower hemolysis, increased albumin and plasma protein adsorption while reduction in fibrinogen adsorption. Further, the platelet adhesion was highly suppressed and significant increase in coagulation period was observed for Clopidogrel incorporated scaffolds. The results of cell adhesion and cell viability substantiate the biocompatibility of the developed nanofibrous scaffolds with the HUVEC cell viability on polyurethane/polyethylene glycol, polyurethane/polyethylene glycol/Clopidogrel-1, 5, and 10% at day 7 found to be 12.35, 13.36, 14.85, and 4.18% higher as compared to polyurethane scaffolds, and the NIH/3T3 cell viability found to be 35.27, 70.82, 36.60, and 7.95% higher as compared to polyurethane scaffolds, respectively. Altogether the results of the study advocate the incorporation of Clopidogrel to the polyurethane/polyethylene glycol blend in order to fabricate scaffolds with appropriate antithrombotic property, hemocompatibility, and cell proliferation capacity and thus, might be successfully used as antithrombotic material for biomedical application.
Keywords: adhesion; cardiovascular; coagulation; electrospinning; Hemocompatible; platelet

Study of interfacial adhesion between nickel-titanium shape memory alloy and a polymer matrix by laser surface pattern - Samal, Sneha; Tyc, Ondrej; Heller, Ludek; Sittner, Petr; Malik, Monika; Poddar, Pankaj; Catauro, Michelina; Blanco, Ignazio (Applied Sciences-Basel, 2020)
The aim of this article is to investigate the interfacial adhesion of Ni-Ti shape memory alloy with a polymer matrix of Poly (methyl methacrylate) (PMMA). The surface pattern on Ni-Ti plates was channeled by a solid state laser machine. The laser machine allows for creating channels on the Ni-Ti surface for infiltration of the PMMA matrix, which could be attached as an intra-surface locking pattern to the Ni-Ti surface. The influence of the PMMA matrix on the surface of the NiTi plate was evaluated by thermomechanical analysis (TMA) and dynamic mechanical analysis (DMA). The surface characterization was carried out by an optical microscope on the PMMA/NiTi composite after mechanical testing. During mechanical testing, the polymer displays the multiple cracks in the longitudinal direction that result in slipping and fracture. TMA and DMA analyses were performed on the Ni-Ti- and PMMA-coated Ni-Ti ribbon to observe elasticity and the storage modulus for both samples. Better adhesion than 80 % was observed in the Ni-Ti surface, in the laser surface pattern, in comparison to the free plain surface. However, the polymer acts as mechanical backing that caused a reduction in the shape-memory properties of the composite material.
Keywords: adhesion; mechanical properties; NiTi composites; NiTi plate; PMMA; Polymer; surface features

Polyethylene-grafted sheet-like silsesquioxane nanocomposites with unprecedented adhesion to polar substrates - Sharma, Vivek; Paulbudhe, Uday; Bachhar, Nirmalya; Chikkali, Samir H.; Kumaraswamy, Guruswamy (ACS Applied Polymer Materials, 2023)
Polyethylene is a highly apolar polymer with very pooradhesionto most substrates, necessitating the use of tie layers. Therefore,the synthesis of functional polyethylene is a long-standing challengein catalytic ethylene polymerization. Here, we report the preparationof a nanocomposite comprising polyethylene covalently grafted ontosheet-like silsesquioxanes, with unprecedented adhesion to metal andglass. A norbornene-grafted, layered Mg-silsesquioxane is treatedwith Grubbs second-generation catalyst (G-II), and the identity ofcovalently tethered G-II is unambiguously ascertained. Covalentlytethered G-II catalyzes the ring opening metathesis polymerizationof cyclooctene to poly(cyclooctene). The resulting poly(cyclooctene)is catalytically hydrogenated to yield polyethylene. This polyethylenenanocomposite exhibited a bonding strength of the order of 100 MPaon stainless steel and aluminum, 10-fold higher than reported forengineered polyethylene copolymers. The nanocomposite exhibits anincrease in the polar component of surface energy, yet remains compatibleand cocrystallizes with a polyethylene matrix.
Keywords: adhesion; clay; Nanocomposite; Polyethylene; silsesquioxane